Arabidopsis ADF5 promotes stomatal closure by regulating actin cytoskeleton remodeling in response to ABA and drought stress. (24th November 2018) - Qian, Dong; Zhang, Zhe; He, Juanxia; Zhang, Pan; Ou, Xiaobin; Li, Tian; Niu, Lipan; Nan, Qiong; Niu, Yue; He, Wenliang; An, Lizhe; Jiang, Kun; et al.
Abstract : ADF5 promotes stomatal closure by regulating actin filament dynamics, and members of the ABF/AREB transcription factor family may serve as potential upstream regulators of ADF5 in the drought stress/ABA signaling pathway. Abstract: Stomatal movement plays an essential role in plant responses to drought stress, and the actin cytoskeleton and abscisic acid (ABA) are two important components of this process. Little is known about the mechanism underlying actin cytoskeleton remodeling and the dynamic changes occurring during stomatal movement in response to drought stress/ABA signaling. Actin-depolymerizing factors (ADFs) are conserved actin severing/depolymerizing proteins in eukaryotes, and in angiosperms ADFs have evolved actin-bundling activity. Here, we reveal that the transcriptional expression of neofunctionalized Arabidopsis ADF5 was induced by drought stress and ABA treatment. Furthermore, we demonstrated that ADF5 loss-of-function mutations increased water loss from detached leaves, reduced plant survival rates after drought stress, and delayed stomatal closure by regulating actin cytoskeleton remodeling via its F-actin-bundling activity. Biochemical assays revealed that an ABF/AREB transcription factor, DPBF3, could bind to the ADF5 promoter and activate its transcription via the ABA-responsive element core motif ACGT/C. Taken together, our findings indicate that ADF5 participates in drought stress by regulating stomatal closure, and may also serve as a potential downstream target of the drought stress/ABA signaling pathway via members of the ABF/AREB transcription factors family.